Synthesis of Nonionic Surfactants. Sugar-Substituted Ether-Linked Bis-1,2,3-Triazoles - Ibrahim Mohammed, Adnan (Asian Journal of Chemistry, 2012)
This work describes the synthesis of sugar-based ether-linked bis-1,2,3-triazoles. In the first approach, in which the heterocyclic portion was constructed from the click 1,3-dipolar cycloaddition of n-octyl azide and n-nonyl azide respectively with propagyl alcohol. Compounds 3 and 4 were readily prepared under phase transfer conditions from the corresponding triazolyl alcohols 1 and 2 and propargyl bromide. Two sugar azides starting from D-glucose and D-galactose were made to react with each of propargyl ethers 3 and 4 under Cu(I)-catalyzed Huisgen-Meldal 1,3-dipolar cycloaddition conditions. This reaction proceeded with excellent regioselectivity to afford the desired 1,4-disubstituted derivatives 5-8 in good yields. Bistriazoles 5 and 6 were deprotected under basic conditions. The effect of compounds 5-10 on the surface tension of water and some organic solvents like m-xylene will be measured in next subsequent study.